The Effect of Service Quality on Students’ Satisfaction Using the Library of Senior High School 1 of Padangsidimpuan - Hanifah Mora Lubis (Journal of Social Science, 2020)
The principle in prioritizing satisfaction is philosophy in the library. One of the many things considered is to provide quality services such as services that can meet students' needs and their expectations. The problem in this research is how to affect the quality of service relibiality, responsiveness, assurance, empathy dan tangibles on student satisfaction in using the library of Senior high school 1 of Padangsidimpuan and to know dimensions of service quality are most influential in students’ satisfication in utilizing the library. Samples taken were 78 people from all of these populations 98 students consisting of students registered as members of the library using the Slovin formula. Data from this research were collected through a questionnaire. nstruments of validity were tested using descriptive analysis supported by survey methods, hypotheses were tested using multiple linear regression with 95% evidence intervals (α = 5%). The results showed that the dimensions of reliability, date power, assurance, empathy and tangibles had a positive influence on student satisfaction of 0.215 with a significant level of 95%. This shows that 21.5% of students' satisfaction in using library of Senior High School 1 of Padangsidimpuan can be influenced by several dimensions such as reliability, responsiveness, assurance, empathy and tangibles and the remaining 78.5% is influenced by other independent variables that have not been displayed. The most influential dimension in satisfying students in using the Library of Senior High School 1 of Padangsidimpuan is the responsiveness dimension.